Khaldiyeh's appearance throughout the Gambakur (Benguel) and the role of her schools In community development - نعيم دونر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
In this research, Khaldiyya studied the emergence of al-Naqshbandi as a main branch of the Naqshbandi method, founded by Maulana Khalid al-Shahrzouri alBaghdadi, in the area of Gambakgor (Bengul). Politically, socially, economically and culturally for the Kurds; because the scholars who studied in the Khalidiya schools had studied in difficult conditions and harsh conditions because religious schools were not available after the proclamation of the republican system; Prevent the teaching of Islamic sciences and Arabic constitutional law in March 1924 3 were studying in mosques and closets afraid of the soldiers and mighty them vigilant, keep Matoun more often in the countryside and shops. Therefore, I believe that my work and its ideals will be a building to preserve our heritage and culture, and an example to introduce our leaders in writing and moving from oral culture to the written culture of the Kurds. Because boredom is reminiscent of its civilization, civilizations are based on the foundations of heritage, the translation of men's flags and their role in the development of society is important in this respect. Civilizations.